Effect of arachidonic and docosahexaenoic acid supplementation on respiratory outcomes and neonatal morbidities in preterm infants. Issue 1 (January 2023) - Wendel, Kristina; Aas, Marlen Fossan; Gunnarsdottir, Gunnthorunn; Rossholt, Madelaine Eloranta; Bratlie, Marianne; Nordvik, Tone; Landsend, Erlend Christoffer Sommer; Fugelseth, Drude; Domellöf, Magnus; Pripp, Are Hugo; Stiris, Tom; Moltu, Sissel Jennifer
Summary: Background & aims: Studies have suggested that supplementation with docosahexaenoic acid (DHA) to preterm infants might be associated with an increased risk of bronchopulmonary dysplasia (BPD). Our aim was to investigate the effect of enteral supplementation with arachidonic acid (ARA) and DHA on short-term respiratory outcomes and neonatal morbidities in very preterm infants. Methods: This is a secondary analysis of data from the ImNuT (Immature, Nutrition Therapy) study, a randomized double blind clinical trial. Infants with gestational age less than 29 weeks were randomized to receive a daily enteral supplement with ARA 100 mg/kg and DHA 50 mg/kg (intervention) or medium chain triglycerides (MCT) oil (control), from second day of life to 36 weeks postmenstrual age. Study outcomes included duration of respiratory support, incidence of BPD and other major morbidities associated with preterm birth. Results: 120 infants with mean (SD) gestational age 26.4 (1.7) weeks were randomized and allocated to either the intervention or control group. Supplementation with ARA and DHA led to a significant reduction in number of days with respiratory support (mean (95% CI) 63.4 (56.6–71.3) vs 80.6 (72.4–88.8); p = 0.03) and a lower oxygen demand (FiO2 ) (mean (95% CI) 0.26 (0.25–0.28) vs 0.29 (0.27–0.30); p = 0.03) compared to control treatment. There were no clinically important differences in incidence of BPD and other major morbidities between the treatment groups. Conclusions: Supplementation with ARA and DHA to preterm infants was safe and might have a beneficial effect on respiratory outcomes. Clinical trial registration: The trial has been registered in www.clinicaltrials.gov, ID: NCT03555019.